Glycosylated cannabinoids in Cannabis sativa and enzyme design to modulate their synthesis - Zoe Pinkas; Olga Khersonsky; Paula Berman; Nikolay Kuzmich; Ilana Rogachev; Sarel J. Fleishman; Asaph Aharoni (Proceedings of the National Academy of Sciences, 2025)
Despite extensive study of its chemical composition and long history of medicinal use, the occurrence of glycosylated cannabinoid derivatives in Cannabis sativa has not been documented to date. Here, we identified glycosylated cannabinoids and their common intermediate olivetolic acid (OA) in various C. sativa tissues and cultivars. We moreover identified four UDP-glycosyltransferases (UGTs) from C. sativa with OA glycosylating activity. Enhancing the water solubility of cannabinoids through glycosylation holds potential for pharmaceutical development and cosmetic applications. However, glycosylation of pathway intermediates such as OA may divert metabolic flux away from cannabinoid production, complicating efforts to engineer glycosylated forms. To resolve this, we applied FuncLib design to an AlphaFold-predicted structure of one of the identified enzymes CsUGT14, generating active-site variants. Through functional screening, we identified mutants that display increased specificity toward cannabinoid end products over the OA intermediate. Moreover, we recognized a single point mutation that dictates OA positioning within the active site, thereby altering isomer formation. These findings expand the known repertoire of natural cannabinoids and provide a rare example of crystallography-free enzyme design to improve stability, substrate selectivity, and isomer specificity. Furthermore, this work lays the foundation for the tailored biosynthesis of soluble glycosylated cannabinoids in heterologous systems.